Delayed hypersensitivity reaction to allopurinol: a case report - Che' Man, Mohamad; Che Alhadi, Shahidah; Wan Mahmod, Wan Fatimah Suriyani; Amiruddin, Salman; Mohd Razib, Mohd Zhafri; Ismail, Rasimah (Academy of Family Physicians of Malaysia (AFPM), 2023)
Allopurinol is the well-known first-line treatment option for symptomatic hyperuricaemia and gout. It is cost-effective particularly for the management of chronic gout. The common early side effects of allopurinol are skin rashes, diarrhoea and nausea. Meanwhile, a dangerous concerning complication is Stevens–Johnson syndrome, which can cause severe morbidity and mortality. Delayed hypersensitivity to allopurinol is rare but should be one of the differential diagnoses if a patient with underlying gout on chronic allopurinol treatment presents with skin rashes. The present case highlights the importance of a high index of suspicion in at-risk patients with underlying gout along with skin rashes on long-term allopurinol treatment to avoid unnecessary patient management.